Refugee and immigrant-background parents’ academic engagement, resources, and children’s adjustment in German lower-income elementary schools - Chwastek, S.; Leyendecker, B.; Jugert, P.; McElvany, N.; Busch, J. (Frontiers in Psychology, 2025)
BackgroundRefugee and recently immigrated (RRI) families in Germany often reside in lower-income, multiethnic neighborhoods alongside many other immigrant-background families. Their children are likely to face barriers to their academic development. Yet, research on how these parents’ academic engagement and resources influence their children’s school adjustment remains scarce. We explored (a) the relations of parents’ academic engagement, resources, and their children’s school adjustment, and (b) the exact forms of parents’ academic engagement and resources, facilitators, and barriers to it.MethodsWe conducted structured telephone-based interviews including closed- and open-format questions with Arabic-speaking refugee (refugee), recently immigrated, immigrant-background, and non-immigrant parents in German lower-income neighborhoods (N = 108). Measures assessed relations between parents’ home and school engagement, parent- and school-related resources (formal education, mental health, German language skills, social support, educational aspirations, knowledge of the German education system, parent-teacher relationship, sense of well-being at school), and children’s elementary school adjustment (socio-emotional adjustment, grades, well-being at school).ResultsMultiple regression analyses revealed that German language skills and participation in local social support groups were related to their home and school engagement. Parents’ academic engagement was not related to children’s school adjustment. RRI parents reported lower levels of resources than immigrant-background and non-immigrant parents, with refugee parents reporting the lowest levels of resources. Descriptive analyses of the open-format questions and single-scale items revealed group differences in parents’ school engagement, home engagement, and resources (e.g., perceived responsibilities, communication with school and other parents). Regarding other dimensions, RRI, immigrant-background, and non-immigrant parents reported similar levels of resources. Additionally, we found indicators of RRI parents’ high academic expectations and willingness to support their children academically.ConclusionOur findings suggest the importance of increasing RRI and immigrant-background parents’ availability of resources to facilitate their academic engagement. Our findings suggest that their children may adjust to school independently of parents’ academic engagement as measured. Future research should examine the contribution of unmeasured (e.g., better culturally adapted) academic engagement forms as well as which school- and community-level factors may compensate for limited parental resources.